1998
DOI: 10.1099/0022-1317-79-2-405
|View full text |Cite
|
Sign up to set email alerts
|

Sequence and in vivo transcription of Lacanobia oleracea granulovirus egt.

Abstract: We have determined the nucleotide sequence and located the major in vivo transcript termini of the Lacanobia oleracea granulovirus (LoGV) egt gene. The open reading frame encodes a 460-amino acid polypeptide having extensive sequence similarity to ten nucleopolyhedrovirus (NPV) ecdysteroid UDPglucosyltransferase (EGT) proteins ; the degree of similarity is particularly high within several previously identified EGT ' domains ', and eight invariant amino acid residues are conserved. A phylogenetic tree, construc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 28 publications
0
12
0
1
Order By: Relevance
“…This enzyme has been reported from several other baculoviruses (O'Reilly, 1995;Smith and Goodale, 1998), and its effects on the development of the Archives of Insect Biochemistry and Physiology host insect and hemolymph ecdysteroid titer have been studied extensively (Park et al, 1993Burand et al, 1996).…”
Section: Introductionmentioning
confidence: 98%
“…This enzyme has been reported from several other baculoviruses (O'Reilly, 1995;Smith and Goodale, 1998), and its effects on the development of the Archives of Insect Biochemistry and Physiology host insect and hemolymph ecdysteroid titer have been studied extensively (Park et al, 1993Burand et al, 1996).…”
Section: Introductionmentioning
confidence: 98%
“…Three candidate late‐promoter motifs and a possible TATA signal with a CATT motif are located upstream from the AdhoGV egt ORF. Primer extension analysis in LaolGV suggested that a low level of egt transcripts initiating a CATT motif and a much higher level of transcripts initiating within a late promoter motif (Smith & Goodale, 1998). In AdhoGV, it is most likely that one or more of these late promoters are used as main initiation sites of egt transcription.…”
Section: Discussionmentioning
confidence: 99%
“…]), Lymantria dispar MNPV (LdMNPV) (Riegel et al ., 1994), Mamestra brassicae MNPV (MbMNPV) (Clarke et al ., 1996), Orgyia pseudotsugata MNPV (Pearson et al ., 1993), S. littoralis MNPV (Smith, unpublished data [GenBank accession no. ]) and Lacanobia oleracea GV (LaolGV) (Smith & Goodale, 1998). The primer sequences are as follows in parentheses; capital letters indicate nucleotides that may vary (I = inosine; K = G or T; Y = C or T; R = A or G; W = A or T) and lowercase letters denote additional residues included to facilitate cloning of the PCR product: EGT + 98 (5′‐ggagaattCCIKCITAYAGICAYCA‐3′) and EGT + 1363 (5′‐gacggatccTCIGTRWACYWRAYIGCYTT‐3′).…”
Section: Methodsmentioning
confidence: 99%
“…Viral strain LoGV‐S1, originally derived from the Scottish wild‐type isolate described by Crook et al. (1982), was cultured by low‐mortality‐dose infection of L. oleracea larvae (Smith & Goodale, 1988; Matthews et al., 2002). The inoculum used in the subsequent experimental investigations consisted of LoGV‐S1 (hereafter referred to as LoGV) occlusion bodies that had been prepared and purified as described by Smith & Crook (1988) and Matthews et al.…”
Section: Methodsmentioning
confidence: 99%